Ultrastructure and histology of organogenesis induced from shoot tips of maize (Zea mays, Poaceae) - Marín-Méndez, Walter (2009)
Shoot tips of maize (Zea mays L.) were cultured on Murashige and Skoog medium supplemented with 2 mg/l BA +1 mg/l 2,4-D +40 mg/l, to investigate phases of ontogenetic development. The study used light microscopy as well as scanning and transmission electronic microscopy techniques. Shoot tips of maize are composed of small cells with a dense cytoplasm and a prominent nucleus. The process of organogenesis began with swelling of the shoot tip, as the first evidence of organogenic calli formation observed three weeks after culture get started. There were two morphologically different types of cells within the organogenic calli. The layer consisted of large cells with small nucleus, free-organelle cytosol, irregular plasmatic membrane, trichomelike structures, and thick cell walls. In the inner cell layer, small and isodiametric cells with a prominent nucleus, small vacuoles, endoplasmatic reticulum, Golgi, mitochondrias and chloroplasts were observed. The presence of trichomes in the more active morphogenic zones could indicate an organogenic potential